Islam, State, and Local Wisdom: An Examination of Widowhood Inheritance Law in Indonesia - Hidayat, Muhammad (Hukum Keluarga Islam IAIN LANGSA, 2024)
This article highlights the urgency of applying the common property distribution approach prior to the distribution of inheritance in the Indonesian context, which is influenced by local wisdom practices. This research aims to emphasize the rights of wives as widows over joint property through the application of the Compilation of Islamic Law (KHI), so that widows can obtain a fairer share before the distribution of their inheritance rights in accordance with the principles of fiqh. The method used in this research is a normative-juridical approach, with document analysis of legal regulations and their application in the context of local wisdom in Indonesia. The findings show that the distribution of joint property, before the distribution of inheritance, is very important to protect the rights of women who are often marginalized in a society that prioritizes the tradition of male lineage. The affirmation of giving half of the joint property to the widow at the beginning of the distribution before the widow receives her inheritance rights can be equated with shirkah that in the context of marriage the wife also contributes to the collection of property. The discussion in this study emphasizes that the integration of fiqh principles and KHI provisions in the distribution of inheritance, by first recognizing the widow's right to joint property, then the widow receives her inheritance rights after the joint property is distributed, this form of model not only ensures that the widow receives a fair share, but also strengthens the position of women in inheritance issues for the welfare of her family.